Col d'Olen, water chemistry (N-NH4) 2008-2019 - Michele Freppaz; Davide Viglietti (Zenodo, 2020)
Dataset provides information about soil temperature, soil C and N dynamics at different sites in the alpine tundra, along an elevational gradient from 2500 to 2900 m asl during the period 2005-2018. Moreover, in ordrer to evaluate how topsoil can influence the quality of surface water, lake water was sampled monthly at the same time that soil was sampled. The N-NH4 concentration is measured in water samples collected in triplicate in two lakes (Cimalegna and Bowditch) from 2008 to 2019. The ongoing studies aimed at investigating how the meteorological variables affect the biogeochemistry of seasonally snow covered areas, with a special focus on the effect of the snow cover duration on soil and water C and N dynamics during the growing season.